DEVELOPMENT OF THE DEFINITION OF SEPSIS - Dimić, Nemanja; Đurić, Marko; Nenadić, Irina; Boboš, Marina; Bojić, Suzana; Vukotić, Tatjana; Simeunović Gojgić, Mirjana; Gojgić, Milan; Stevanović, Predrag; Bojović, Ksenija (Srpski medicinski časopis Lekarske komore, 2023)
Sepsis is a significant health problem, considering that, annually, over 20 million people fall ill from sepsis. Despite the significant development of medicine in recent decades, the mortality rate of sepsis is exceptionally high (about 26%). The definition of sepsis developed together with the understanding of the mechanism of sepsis. At the beginning of the 1990s, the first definition of sepsis was created, according to which sepsis was defined as systemic inflammatory response syndrome (SIRS), with the presence of suspicion or evidence of infection. Due to many inadequately diagnosed patients with sepsis, another definition was created, according to which sepsis is defined as a clinical syndrome. As the result of the lack of clarity of the previous definitions and the new information on the pathophysiological process of sepsis, a third definition of sepsis was developed in 2016. According to this definition, sepsis is a life-threatening condition based on organic dysfunction resulting from the body's inappropriate response to infection. Septic shock manifests as circulatory, cellular and metabolic instability. It is characterized by a serum lactate level higher than 2 mmol/l and hypotension, which requires vasopressor therapy after the administration of intravenous solutions. This definition of sepsis and septic shock enables early recognition and treatment of patients with sepsis, which are critical steps in reducing the incidence and mortality from this disease.
Keywords: sepsis; definition; mortality